Excellence of children in Islam - Seyyed Mohammad Hosseini, Ali esfehanian Semnani, Seyyed Mohammad Moosavi Bojnourdi, (Opción, 2019)
The aim of the study is to examine the context of the interaction of education and jurisprudence in the life of children in an Islamic society through comparative studies of both issues. As a result, a child who becomes dominant in himself and has grown up inside and able to correct his relationship with God in the course of his spiritual growth will also succeed in correcting his relationship with others. As a conclusion, the admission of jurisprudence is the provider of this educational dimension, and in this regard, acts such as prayer, fasting and pilgrimage play a decisive role.